PENGARUH UTANG TERHADAP LABA BERSIH PT INDOCEMENT TUNGGAL PRAKASA TBK TAHUN 2021 - Nurdin Zaelani Apdau; Riko Sutriyadi; Nasril Nasril (POLITEKNIK LP3I JAKARTA, 2021)
With the rapid growth of the present day, every company is required to be able to compete with other companies in establishing the development and the existing rates. The company's growth and progress are determined in how it achieves its ultimate goal of achieving its established profit. In this case debt isa source of funds to continue production and achieve the company's goals. The thesis marked